2020
DOI: 10.4102/sajip.v46i0.1707
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coachee personality traits, propensity to trust and perceived trustworthiness of a coach, on a coachee’s trust behaviour in a coaching relationship

Abstract: Heyns, M. (2020). The impact of coachee personality traits, propensity to trust and perceived trustworthiness of a coach, on a coachee's trust behaviour in a coaching relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Gillespie's (2003; relatively more recent definition of trust has intensified the need to understand how trust decisions develop from an individual perspective and how they relate to other trust-relevant variables (Van der Werff and Buckley, 2017). To illustrate: A recent study by Terblanche and Heyns (2020) showed that neither personality traits nor propensity to trust are predictors of the trust behavior of a trusting party toward a coach within a coaching relationship. Only perceived trustworthiness predicted both reliance and disclosure-based trust in a coach.…”
Section: A Person-centered Approach To Trustmentioning
confidence: 99%
“…Gillespie's (2003; relatively more recent definition of trust has intensified the need to understand how trust decisions develop from an individual perspective and how they relate to other trust-relevant variables (Van der Werff and Buckley, 2017). To illustrate: A recent study by Terblanche and Heyns (2020) showed that neither personality traits nor propensity to trust are predictors of the trust behavior of a trusting party toward a coach within a coaching relationship. Only perceived trustworthiness predicted both reliance and disclosure-based trust in a coach.…”
Section: A Person-centered Approach To Trustmentioning
confidence: 99%
“…For example, extraversion positively associated with self-reported benefits of coaching (Jones et al, 2014), while openness, conscientiousness and emotional stability positively predicted client's selfreported transfer of learning (Stewart et al, 2008). However, studying mean levels of the Big Five traits has produced sparse findings, which are mostly descriptive rather than explanatory in nature (Terblanche and Heyns, 2020).…”
Section: Affect Behavior Cognition and Desire In Personality Traitsmentioning
confidence: 99%
“…, 2008). However, studying mean levels of the Big Five traits has produced sparse findings, which are mostly descriptive rather than explanatory in nature (Terblanche and Heyns, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Conscientiousness is described as an individual's inclination to demonstrate self-discipline and strive for skill and accomplishment (Greenberg 2011). Conscientiousness categorises people into those who are rational, informed and consider themselves to be competent (Terblanche & Heyns 2020). This personality dimension is clarified by limited characteristics such as being well organised, cautious, selfdisciplined, accountable and accurate at the high end and being disorganised, impulsive, careless and undependable at the low end (Bell & Njoli 2016).…”
Section: Conscientiousness and Habitual Facebook Usagementioning
confidence: 99%